Access of rural women to institutional credit :issues and alternatives - Malhotra, Rakesh; Bankers Institute of Rural Development (Lucknow : Bankers Institute of Rural Development, 2000)
Study with reference to Rae Bareily District, India.
Includes statistical tables.
Keywords: Women -- India -- Social conditions; Rural women -- India -- Rae Bareli (District) -- Economic conditions -- Statistics; Rural credit -- India -- Rae Bareli (District) -- Case studies; Rural development -- India -- Rae Bareli (District) -- Case studies